Resource: Mapping the Triticum aestivum proteome. (1st February 2017) - Duncan, Owen; Trösch, Josua; Fenske, Ricarda; Taylor, Nicolas L.; Millar, A. Harvey
Summary: Yield and quality improvement of bread wheat ( Triticum aestivum) is a focus in efforts to meet new demands from population growth and changing human diets. As the complexity of the wheat genome is unravelled, determining how it is used to build the protein machinery of wheat plants is a key next step in explaining detailed aspects of wheat growth and development. The specific functions of wheat organs during vegetative development and the role of metabolism, protein degradation and remobilisation in driving grain production are the foundations of crop performance and have recently become accessible through studies of the wheat proteome. We present a large scale, publicly accessible proteome mapping of wheat consisting of 24 organ and developmental samples. Tissue specific sub‐proteomes and ubiquitously expressed markers of the wheat proteome are identified, alongside hierarchical assessment of protein functional classes, their presence in different tissues and correlations between the abundance of functional classes of proteins. Gene‐specific identifications and protein family relationships are accounted for in the organisation of the data and 202 new protein‐coding transcripts identified by proteogenomic mapping. The interactive database will serve as a vehicle to build, refine and deposit confirmed targeted proteomic assays for wheat proteins and protein families to assess function (www.wheatproteome.org ). Significance statement: Determining how the wheat genome is used to build the proteome is necessary to explain detailed aspects of wheat growth and development. Here we present large‐scale proteomic datasets of 24 wheat tissues, enabling dissection of tissue‐specific proteomes, correlation of transcript and protein data for different wheat tissues and protein functional classes, and identification of constitutive and differential proteome markers for a variety of applications. In addition, we identified new proteins not predicted from the draft wheat genome.